Physical and Muscular Performance in a Professional Soccer Player with a Posterior Cruciate Ligament Injury Following an Isokinetic Exercise Program: A Case Report - Fernanda QRC Mostagi; Pedro AC Silva; Giovana R Munaro; Raiane G Marcato; Daniel B Nampo; Gabriel F Santiago; Karen Obara; Jefferson R Cardoso (International Journal of Sports Physical Therapy)
# Background and Purpose